Sediment Fallout Rates in Tanjung Rhu Coral Reefs - Anisah Lee Abdullah,; Zulfigar Yasin,; Brian R. Shutes,; Mark Fitzsimons, (Kajian Malaysia, 2011)
This study was conducted in Tanjung Rhu, Pulau Langkawi, which is located in the northwest of Peninsular Malaysia. The objective of this study was to measure and compare the sediment fallout rates of Teluk Dedap in Tanjung Rhu with its control site in Teluk Datai during the wet and dry seasons to shed light on the sedimentation problem faced by the coral reefs of north Pulau Langkawi. Sediment fallouts were collected from the spring tidal periods of both the wet and dry seasons. Results showed that sediment fallout rates in Tanjung Rhu were 1,403.48 ± 125.60 g/m2 /day (dry season) and 6,550.77 ± 641.43 g/m2 /day (wet season). In Teluk Datai the sediment fallout rates were 1,532.99 ± 201.81 g/m2 /day (dry season) and 12,446.45 ± 237.81 g/m2/day (wet season). Sediment fallout rate is typically lower during the dry season compared to the wet season, and it is lower on the reef flats than the reef slopes. Paired sample t-tests revealed that there were significant differences in the sediment fallout on the reef flats and reef slopes. Sediment fallout was significantly higher on the reef flat than the reef slopes for both sampling locations during both the dry and wet seasons. However, based on a single-factor ANOVA (p = 0.05), no significant difference was observed between the overall sediment fallout and fallout rates between the two sampling locations during the dry and wet seasons. Microscopic analysis was also performed to examine the possible composition of the analysed sediment fractions. Results showed that the main components of the coarser sediment fractions were biogenic materials and lithified sediments, while for the finer sediment fractions, the main components were feldspar and siliceous and quartz materials.